Estimating the trend of M3 income velocity underlying the reference value for monetary growth - Claus Brand; Dieter Gerdesmeier; Barbara Roffia (European Central Bank (ECB), 2002)
This paper documents the analytical work that was carried out for the 2001 review of the assumption for the trend in M3 income velocity used to calculate the reference value for M3 growth. We analyse the medium-term trend in velocity using univariate time series tools and different money demand models. In addition, some cross-checking is carried out to address data compilation issues related to the accession of Greece in 2001 and to different weighting schemes used to aggregate historical euro area data. It is found that the trend decline in M3 incomevelocity over the medium term is within a range of 1/2% to 1% per year.
Keywords: 330; Geldmenge; Geldumlaufgeschwindigkeit; EU-Staaten